2011
DOI: 10.1111/j.1542-2011.2011.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ Perceptions of Providing Stop‐Smoking Advice and Pregnant Smokers’ Perceptions of Stop‐Smoking Services Within the Same Deprived Area of London

Abstract: In theory, many of the perceived barriers to providing advice could be overcome by implementing effective mandatory training for midwives. However, real issues, such as lack of time, have a major impact on the provision of advice. Pregnant smokers expect and appreciate receiving stop-smoking advice from midwives. Yet, they tend to have negative expectations of stop-smoking services, although the experiences of those who have attended these services are positive. Raising awareness of stop-smoking support for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 26 publications
2
71
0
Order By: Relevance
“…[110][111][112][113][114][115][116][117][118][119][120] This is a consistent finding in the literature that has been described since members of our team first conducted research with disadvantaged women in the 1970s. 151 The importance of smoking to reduce stress was also described by partners and HPs.…”
Section: Stress and Enjoymentsupporting
confidence: 74%
See 1 more Smart Citation
“…[110][111][112][113][114][115][116][117][118][119][120] This is a consistent finding in the literature that has been described since members of our team first conducted research with disadvantaged women in the 1970s. 151 The importance of smoking to reduce stress was also described by partners and HPs.…”
Section: Stress and Enjoymentsupporting
confidence: 74%
“…113,133,[162][163][164][165][166][167][168] The synthesis identified that both the professional role of participants and the organisational context in which they worked could act as either barriers to or facilitators of an individual's ability to provide smoking cessation support to pregnant or postpartum women. Underpinning these factors was an acknowledgement that the association between maternal smoking and social disadvantage was a considerable barrier to addressing and supporting smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
“…This includes not raising the topic when a negative reception is anticipated and variable rates of referral due to the offer of choice (opt‐in) or not (opt‐out). Addressing either smoking or obesity is likely to be compounded by the perceived lack of time among health care professionals, particularly midwives, to address lifestyle behaviour change (Abatemarco et al ., 2007; Herberts & Sykes, 2012) and a prioritization for discussing the clients’ concerns, usually about labour (Flemming et al ., 2016), during consultations.…”
Section: Discussionmentioning
confidence: 99%
“…Professionals commonly report feeling that they lack the skills, confidence, motivation, and the time to address, discuss, and advise on smoking (Colomar et al ., 2015; Flemming et al ., 2016; Herberts & Sykes, 2012). These are not clearly addressed by training in brief advice (Althabe et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation